The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/rda.13773
|View full text |Cite
|
Sign up to set email alerts
|

Post‐mortem recovery, in vitro maturation and fertilization of fallow deer (Dama dama, Linnaeus 1758) oocytes collected during reproductive and no reproductive season

Abstract: In recent decades, concern about nature conservation has grown rapidly as a consequence of accelerating rates of natural habitat loss, fragmentation and degradation that have resulted in the extinction of several species (Haddad et al., 2015). Assisted reproductive techniques (ARTs) and genetic rescue banks (GRBs) are useful tools to cope with fragmentation of habitats and loss of genetic variability (Zachos, 2011). In ungulates, ARTs' application could permit a more rapid expansion of populations than natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
1
1
Order By: Relevance
“…Apoptotic sperm can be also responsible for the loss of human embryos in the early stages of development [ 33 ]. Therefore, the highest number of cleaved embryos and blastocysts we measured was in the group fertilized with sperm stored for one day, and the results were lower than those reported by other authors who conducted IVF with cryopreserved sperm [ 34 , 35 ]. Thus, storage-induced changes in sperm, embryonic development affected by oocyte quality, in vitro culture conditions such as temperature, and the applied culture media [ 36 , 37 ] are all aspects demanding further study.…”
Section: Discussioncontrasting
confidence: 70%
“…Apoptotic sperm can be also responsible for the loss of human embryos in the early stages of development [ 33 ]. Therefore, the highest number of cleaved embryos and blastocysts we measured was in the group fertilized with sperm stored for one day, and the results were lower than those reported by other authors who conducted IVF with cryopreserved sperm [ 34 , 35 ]. Thus, storage-induced changes in sperm, embryonic development affected by oocyte quality, in vitro culture conditions such as temperature, and the applied culture media [ 36 , 37 ] are all aspects demanding further study.…”
Section: Discussioncontrasting
confidence: 70%
“…Moreover, the fertilization rate depends on the reproductive status when oocytes are collected; results of our study [25] and the Berg and Asher [41] study showed low fertilization rates during the no-breeding season. The content of the medium during IVF also plays an important role because even if successful fertilization occurs, further embryo development may be inhibited or finished before the blastocyst stage when the culture conditions are not proper, as in a study on fallow deer [42]. In the case of cervids, of interest is research connected with the differences in zona pellucida (ZP) content in selected Cervidae species that may cross naturally, e.g., Cervus elaphus and Cervus nippon [43].…”
Section: In Vitro Maturation (Ivm)mentioning
confidence: 99%